The Dystonia Coalition: A Multicenter Network for Clinical and Translational Studies - Kilic-Berkmen, Gamze; Wright, Laura J.; Perlmutter, Joel S.; Comella, Cynthia; Hallett, Mark; Teller, Jan; Pirio Richardson, Sarah; Peterson, David A.; Cruchaga, Carlos; Lungu, Codrin; Jinnah, H. A. (Frontiers in Neurology, 2021)
Dystonia is a movement disorder characterized by sustained or intermittent muscle contractions causing abnormal postures, repetitive movements, or both. Research in dystonia has been challenged by several factors. First, dystonia is uncommon. Dystonia is not a single disorder but a family of heterogenous disorders with varied clinical manifestations and different causes. The different subtypes may be seen by providers in different clinical specialties including neurology, ophthalmology, otolaryngology, and others. These issues have made it difficult for any single center to recruit large numbers of subjects with specific types of dystonia for research studies in a timely manner. The Dystonia Coalition is a consortium of investigators that was established to address these challenges. Since 2009, the Dystonia Coalition has encouraged collaboration by engaging 56 sites across North America, Europe, Asia, and Australia. Its emphasis on collaboration has facilitated establishment of international consensus for the definition and classification of all dystonias, diagnostic criteria for specific subtypes of dystonia, standardized evaluation strategies, development of clinimetrically sound measurement tools, and large multicenter studies that document the phenotypic heterogeneity and evolution of specific types of dystonia.